Assessment of Vitamin D3 Level Among a Sample of Type 2 Diabetic Patients Attending Diabetes and Endocrinology Center in Al-Hilla City - Ahmed Mahdi Habeeb; Atta Ah Mousa Al-Sarray; Ali Hussein Al Hafidh; Rafah Sabah Barrak; Afraa Brahim (Journal of Techniques)
Vitamin D is found in foods in two primary forms: cholecalciferol (vitamin D3) and ergocalciferol (vitamin D2), with vitamin D3 being a fat-soluble vitamin.  that is necessary for calcium homeostasis and the maintenance of proper function in a variety of tissues. Humans get vitamin D from their diets or from being exposed to ultraviolet B radiation from the sun. Aside from its well-known effects on bone health, vitamin D has been hypothesized to play a role in various disease states and health situations, such as cardiovascular disease and type 2 diabetes. To assess vitamin D3 concentration in patients with type 2 diabetes, using the Vitamin D Total III kit on the Cobas E 411 device. A total of 300 people were recruited, with 150 people suffering from type 2 diabetes serving as cases and 150 healthy volunteers of the same gender and age being used as the control group. Both genders were represented, with an age group between 30 – 79 years. The collection of data lasts for five months, beginning Started in November 2022 to April 2023. The data was analyzed with the readily available statistical package SPSS-28, and Chi-square tests were used to evaluate the relationship among vitamin D, T2DM, and control. Data were provided in simple frequency, percentage, mean, standard deviation, and range measures. Type 2 diabetes patients' mean ± SD ages were 55.4 ± 10.1, while controls had a mean ± SD of age of 55.3 ± 10.0. the sociodemographic features of T2DM and participant control. Shows A statistically significant association was found in the variables of age groups, school level (P = 0.0001), and marital status (P = 0.008). The BMI: mean ± SD (29.69 ± 5.14) of T2DM was higher than the BMI: mean ± SD (24.41 ± 1.95) of controls, as well as the waist-to-height ratio, which showed that the mean ± SD (0.527 ± 0.046) of T2DM was greater than the control mean ± SD (0.483 ± 0.019) at level (P = 0.0001); T2DM patients had deficient and insufficient vitamin D3 levels (38.7% and 33.3%, respectively), whereas controls had deficient and insufficient vitamin D3 levels (28.7% and 30.0%, respectively). It was found that there is a significant difference between low vitamin D3 levels and individuals with type 2 diabetes, and A lack of vitamin D3 is related to an increased risk of developing T2DM.